Heat and PAHs Emissions in Indoor Kitchen Air and Its Impact on Kidney Dysfunctions among Kitchen Workers in Lucknow, North India - Singh, Amarnath (PLoS One, 2016)
Indoor air quality and heat exposure have become an important occupational health and safety concern in several workplaces including kitchens of hotels. This study investigated the heat, particulate matter (PM), total volatile organic compounds (TVOCs) and polycyclic aromatic hydrocarbons (PAHs) emissions in indoor air of commercial kitchen and its association with kidney dysfunctions among kitchen workers. A cross sectional study was conducted on 94 kitchen workers employed at commercial kitchen in Lucknow city, North India. A questionnaire-based survey was conducted to collect the personal and occupational history of the kitchen workers. The urine analysis for specific gravity and microalbuminuria was conducted among the study subjects. Indoor air temperature, humidity, wet/ dry bulb temperature and humidex heat stress was monitored during cooking activities at the kitchen. Particulate matter (PM) for 1 and 2.5 microns were monitored in kitchen during working hours using Hazdust. PAH(S) in indoor air was analysed using UHPLC. Urinary hydroxy-PAHs in kitchen workers were measured using GC/MS-MS. Higher indoor air temperature, relative humidity, PM(1) and PM(2.5) (p<0.001) was observed in the kitchen due to cooking process. Indoor air PAHs identified are Napthalene, fluorine, acenaphthene, phenanthrene, pyrene, chrysene and indeno [1,2,3-cd) pyrene. Concentrations of all PAHs identified in kitchen were above the permissible OSHA norms for indoor air. Specific gravity of urine was significantly higher among the kitchen workers (p<0.001) as compared to the control group. Also, the prevalence of microalbuminuria was higher (p<0.001) among kitchen workers. Urinary PAH metabolites detected among kitchen workers were 1-NAP, 9-HF, 3-HF, 9-PHN and 1-OHP. Continuous heat exposure in kitchens due to cooking can alter kidney functions viz., high specific gravity of urine in kitchen workers. Exposure to PM, VOCs and PAHs in indoor air and presence of urinary PAHs metabolites may lead to inflammation, which can cause microalbuminuria in kitchen workers, as observed in the present study.